2019
DOI: 10.1016/j.omtn.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Expression Profiling and the Potential Role of hsa_circ_0089172 in Hashimoto’s Thyroiditis via Sponging miR125a-3p

Abstract: Circular RNA (circRNA) is a novel subclass of noncoding-RNA molecules that participate in development and progression of a variety of human diseases via sponging microRNAs (miRNAs), but the role of circRNAs in Hashimoto's thyroiditis (HT) has not been defined. In this study, peripheral blood samples from five patients with HT and five healthy volunteers were investigated by Illumina HiSeq Sequencer. A total of 627 differentially expressed circRNAs including 370 upregulated and 257 downregulated ones were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…Non-coding RNAs are well-known to play crucial roles in the pathogenesis of HT (5,6). MicroRNAs (miRNAs or miRs) are a class of small non-coding endogenous RNA molecules of ∼22 nucleotides in length that are involved in the posttranscriptional regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Non-coding RNAs are well-known to play crucial roles in the pathogenesis of HT (5,6). MicroRNAs (miRNAs or miRs) are a class of small non-coding endogenous RNA molecules of ∼22 nucleotides in length that are involved in the posttranscriptional regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies found that hsa_circ_0009910 was overexpressed in osteosarcoma and ovarian cancer cells, acting as a sponge of miR-449a and promoting the expression of miR-449a target IL6R in osteosarcoma while suppressing miR-145 in ovarian cancer cells [ 31 , 32 ]. The expression of hsa_circ_0089172 was up-regulated in Hashimoto’s thyroiditis patients and might function via sponging miR-125a-3p [ 33 ]. However, the role of hsa_circ_0049783 has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding circRNAs have received increasing attention as novel biomarkers for the diagnosis and treatment of diseases, such as gastric cancer, hepatocellular carcinoma, hypertension, diabetes and rheumatoid arthritis, primarily due to their highly conserved sequences and high stability in mammalian cells compared with that in other non-coding miRNAs and lncRNAs ( 25 , 34 , 35 ). Xiong et al ( 36 ) analyzed differences in the circRNA expression level in peripheral blood samples from 5 patients with Hashimoto's thyroiditis and 5 healthy volunteers, and identified 627 differentially expressed circRNAs in the patients with Hashimoto's thyroiditis. Upregulated hsa_circ_0089172 expression was confirmed using RT-qPCR, whilst in vitro experiments revealed that hsa_circ_0089172 could be a potential diagnostic biomarker, as it plays a crucial role in the pathogenesis of Hashimoto's thyroiditis by sponging miR-125a-3p.…”
Section: Discussionmentioning
confidence: 99%